CAPGEN/Online: a fourth generation language - Ahmed, Iftikhar (Animo Repository, 1992)
The CAPGEN/Online (Cobol Application Program Generator/Online) is a fourth generation language that provides a bridge on third-generation language to provide the powers of third-generation language and productivity of fourth-generation language. The approach of CAPGEN/Online is to minimize the system development time, provide the modifiable source code in third-generation language. In this thesis, the complete design of language is presented with the grammar of the language. Design and implementation of compiler for CAPGEN/Online language is also presented. To build simple tasks quickly, an application generator is also designed and implemented. The application generator has ready-made designed programs (which simply define the requirement) and also self-designed programs in which user can design one's own screen to ask several things from the application generator. The application generator generates the program in CAPGEN/Online language which is compiled by compiler converting it in object codes.